Teamwork for defending against the pivot player - Francisco Manuel Ávila Moreno (Federación Extremeña de Balonmano; University of Extremadura, 2015)
Firstly, this writing deals with a key factor for building any defense in handball: how to defend against the pivot player. Under a holistic view of the handball play, the influence of this attacker in the play is analyzed, from how his positions can develop some strategies in attack to the efficient use of movements and blockades. Secondly the principles for a compact zone defense are stated and developed. Based on these principles the writer proposes specific defensive solutions for solving the play situations that are described at the beginning of the writing. Finally the reader can find an essential list of methodological lines for building this kind of defense.